MOLECULAR GENETIC IDENTIFICATION OF SOME SPECIES OF TRUE SHIELD BUGS (PENTOTOMIDAE) (Scientific journal of the Fergana State University, 2025)
This article presents the molecular genetic identification of Bagrada abeillei and Bagrada kaufmanni, species newly recorded for the fauna of Uzbekistan from the Northwestern region of the country. Molecular studies examined the nucleotide sequences in the mitochondrial COI region of these species, confirming their status as distinct species. Additionally, all analysis results of the nucleotide sequences in the mitochondrial COI region for Bagrada abeillei, Bagrada kaufmanni, and Chlorochroa pinicola from the family Pentatomidae were first uploaded to the GenBank database of the National Center for Biotechnology Information (NCBI).